Collaborative Governance (Collaborative Study of Actors in Handling the Spread of Covid-19 in Indonesia) - Indarto, Kus; Ratnawati, Susi (Utan Kayu Publishing, 2021)
The purpose of this study is to analyze the collaboration of actors in handling the spread and the inhibiting factors in handling the spread of Covid-19 in Indonesia.Methodology: This study uses a qualitative approach, with a descriptive method. Data were obtained by studying literature, then analyzed by using interactive model data analysis. The areas studied are Gianyar Regency, Probolinggo City, and Padang City.The collaboration of actors in the Gianyar Regency involves the Indonesian Youth National Committee and the Youth Officers Unit to Fight Covid-19. The collaboration of actors in Probolinggo City involves the local government, academics, and the community. Meanwhile, the collaboration actors in Padang City involve academics, the public, the private sector, local government, and the mass media. And all can be said to go well.Â The collaboration of actors in the areas studied has been going well, although the actors involved are different.